Joint kinetics in maximum velocity sprint running - Bezodis, I.; Salo, A.; Kerwin, D. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The effect of variations in joint kinetics on step characteristics and velocity is not yet known. To investigate contributions from the ankle, knee and hip to maximum velocity sprint running, data were collected from four well-trained male sprinters performing maximum effort 60 m sprints. High-speed video (200 Hz) and ground reaction force (1000 Hz) data were collected at the 45 m mark. Horizontal velocity and joint kinetics, via inverse dynamics, were calculated for two trials in each athlete. The magnitude of positive work performed by the ankle joint during the propulsive phase of stance was closely linked to the velocity of the step, and thought to be the result of a coordinated leg action during the support phase. The study revealed the potential for athlete-specific biomechanical analyses to aid the technical work of athletes and their coaches.